Gamification in Computer Science Education: A Study on Its Effectiveness in Improving Learning Motivation - Harmonvikler D. Lumban Raja (Universitas Advent Surya Nusantara, 2025)
The increasing digitalization of educational systems has raised significant concerns about the security, privacy, and integrity of student data. Traditional centralized data management systems are vulnerable to cyberattacks, data manipulation, and breaches, which necessitate more secure and privacy-preserving solutions. This study aims to explore the integration of blockchain and federated learning as a combined approach to secure educational data management. A systematic literature review methodology was employed to examine relevant studies on the application of blockchain and federated learning in education. The review identified key themes such as blockchain’s potential to provide transparency, immutability, and security, while federated learning enables privacy-preserving data analysis without sharing sensitive information. The findings suggest that the integration of these technologies offers a promising solution to the challenges of managing educational data, enhancing both security and privacy. This study contributes to the academic literature by presenting a conceptual framework that combines blockchain and federated learning for secure and efficient educational data management. The implications of this work extend to policy and practice, particularly in ensuring regulatory compliance and data protection in educational institutions, and provide important lessons for future research on the scalability and practical implementation of these technologies in real-world educational settings.